The nexus between the financial development and CO2 emissions: fresh evidence through time–frequency analyses - Faik Bilgili; Erhan Muğaloğlu; Sevda Kuşkaya; Javier Cifuentes-Faura; Kamran Khan; Mohammed Alnour (Financial Innovation)
Abstract Climate change and environmental degradation threaten the world and global economic conditions. As one of countries’ most important economic components, the financial sector might be an effective tool for reducing and even reversing environmental degradation. The financial sector can affect sustainability through its lending and investment practices. The sector can play a role in financing sustainable projects and businesses, helping reduce CO2 emissions. By aligning its financial objectives with environmental protection, the financial sector can support the transition to a more sustainable future by helping reduce environmental degradation’s negative impacts. This paper examines the domestic financial sector’s impact on CO2 emissions in the United States over the 1990:Q1–2022:Q3 period. In this research, the nexus between the domestic financial sector (total debt securities, loans, liabilities, and total financial assets) and Carbon dioxide emissions in the U.S. is investigated by Morlet wavelet analysis. Rest of the world: sector discrepancy transactions, rest of the world: debt securities and loans, gross domestic product, and the square of the gross domestic product, are control variables in the estimated models. Partial wavelet coherency analyses prove that the financial sector reduces CO2 emissions at the 5–8-year frequency band during different subsample periods. The financial sector’s instruments can be effective in struggling with climate change.